In situ surface derivation of an Fe–Co–Bi layer on an Fe-doped Co3O4 nanoarray for efficient water oxidation electrocatalysis under near-neutral conditions. Issue 14 (24th March 2017) - Zhu, Guilei; Ge, Ruixiang; Qu, Fengli; Du, Gu; Asiri, Abdullah M.; Yao, Yadong; Sun, Xuping
Abstract : A core–shell Fe–Co3 O4 @Fe–Co–Bi nanoarray (Fe–Co3 O4 @Fe–Co–Bi/CC) acts as a superior catalyst electrode for water oxidation, with the need of an overpotential of 420 mV to drive 10 mA cm −2 in 0.1 M K-Bi. Abstract : Developing high-performance water oxidation electrocatalysts working under mild conditions is highly desirable, but still remains challenging. In this communication, we report the in situ surface derivation of an Fe–Co–Bi layer (4–7 nm in thickness) on an Fe-doped Co3 O4 nanowire array supported on carbon cloth (Fe–Co3 O4 /CC). As a 3D catalyst electrode for water oxidation, such a core–shell Fe–Co3 O4 @Fe–Co–Bi nanoarray (Fe–Co3 O4 @Fe–Co–Bi/CC) demonstrates superior activity over that of a Co3 O4 -derived nanoarray catalyst, with the need of an overpotential of 420 mV to drive a geometrical catalytic current density of 10 mA cm −2 in 0.1 M potassium borate (pH = 9.2). Notably, this catalyst also shows good long-term stability with high turnover frequencies.